KAJI EKSPERIMENTAL SAMBUNGAN ADHESIF LAPIS TUNGGAL DAN GANDA AKIBAT PEMBEBANAN TARIK - I Wayan Suweca; Hernansjah Hernansjah; Soni Taufani (Mesin, 2001)
This paper presents an experimental investigation of the single and double adhesively lap-bonding joint. The adhesive material used is Metalloam® grade III. The study was performed to investigate the influence of curing time on the shear strength of the bonding. The results show that the shear strength of the bonding joint increases with the curing time. The maximum shear strength was achieved after the curing time attaint 96 hours.